SISTEM INFORMASI EDUKASI REKAM MEDIS BERBASIS WEB DAN MOBILE - Muhammad Syafi’i; Muhammad Rashif Anshari; Husin Husin (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
Utilization of websites and applications can be in the form of presenting the information needed and providing opportunities for students to access topics anytime, anywhere. The author took the initiative to design and build a web and mobile-based medical record education information system and health information which is an alternative in education related to the scope of Medical Record and Health Information science. The method used in this study is a descriptive method with a quantitative approach. The research design used is a research and development design, is a research design used to produce certain products and test the effectiveness of these products (Sugiyono, 2010). The development procedure in this study uses the waterfall model which is a software development process that is carried out sequentially. The system design is designed with the wordpress platform and IDE (Integrated Development Environment) consisting of VS Code and Flutter. The system design was tested by 3 experts in their field with a validation form, with the results in the form of comments on the improvement of the system design and the interpretation of the system design score. The results of the validation of the system design that are made fall into the feasible category but still need further improvements to perfect the system that will be operated later. The design of this system can be further developed later by further researchers by taking into account some of the shortcomings that exist in the design of this system.